IEEE 1988 Ultrasonics Symposium Proceedings.
DOI: 10.1109/ultsym.1988.49381
|View full text |Cite
|
Sign up to set email alerts
|

Accurate determination of material constants of piezoelectric crystal from SAW velocity measurements

Abstract: e15 e22 [C/m21 e31 e33 W m 2 l 4 3 I601 4 1 kol AbstractA nonlinear least squares algorithm to determine the material constants of LiNbO3 from primary SAW velocity measurements is shown. If at least to some accuracy the values of the mass density p and the unclamped permittivities are known, all 13 independent elastic, piezoelectric and dielectric constants are obtained with high precision. This method is not restricted to LiNbO3 only, but can be applied to other strong coupling materials as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…; Π 77 =e −jkβ (7) ·b · C 13 · a (7) (6) ·b · a (6) 3 + β (6) · a (6) 1 ; Π 87 =e −jkβ (7) ·b · a (7) 3 + β (7) · a (7) 1 ; Π 88 =e −jkβ (8) ·b · a The four eigenvalues in the coating layer (n = 1, 2, 3, and 4) are given by:…”
Section: Appendix Matrix Elements Of the Dispersion Relation Of The Smentioning
confidence: 99%
See 2 more Smart Citations
“…; Π 77 =e −jkβ (7) ·b · C 13 · a (7) (6) ·b · a (6) 3 + β (6) · a (6) 1 ; Π 87 =e −jkβ (7) ·b · a (7) 3 + β (7) · a (7) 1 ; Π 88 =e −jkβ (8) ·b · a The four eigenvalues in the coating layer (n = 1, 2, 3, and 4) are given by:…”
Section: Appendix Matrix Elements Of the Dispersion Relation Of The Smentioning
confidence: 99%
“…In principle, multiparameters can be obtained by such a procedure. For example, Kovacs et al [7] showed that if reasonable initial values of the mass density and the unclamped permittivities are known, then all 13 independent elastic, piezoelectric, and dielectric constants could be obtained with high precision. In most circumstances, however, such a procedure is impractical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all five complex piezoelectric constants, a numerical least square method was used to fit the material constants to the complex wave number of a Rayleigh wave measured with a low frequency (200-600 kHz) SAW device [22], [23]. In comparison with electric impedance methods [10], [14], [18], [24], this technique has the advantage that several of the five piezoelectric constants are obtained simultaneously with good accuracy from one measurement [25], [26], and the measurement can be done at multiple frequencies of interest with one PVDF film by simply changing the inter-digital transducer (IDT) period in the SAW device. To check the validity of the bulk wave through-transmission method, the impedance analyzer, and the least square fitting technique, the same techniques were applied to lead zirconate titanate (PZT)-5H, and the results were compared with known values [27].…”
Section: Introductionmentioning
confidence: 99%
“…which is approximately half the value of the coiipliiig factor, defines the coupling of an electric excitation i1it.o an elastic deformation [7]. Since the substrate properties are known [8], the unknown properties of the two films can be found [9][10]. A least square fit or experimentally measured group velocity values of t h e t,wo different films to theoretically predicted values yields the unknown elastic constants and the tleiisities of the aluminum and the oxide layer.…”
Section: Results and Measurementsmentioning
confidence: 99%